2018 AHA/ACC/AACVPR/AAPA/ABC/ACPM/ADA/AGS/APhA/ASPC/NLA/PCNA Guideline on the Management of Blood Cholesterol: Executive Summary. Issue 25 (18th June 2019) - Grundy, Scott M.; Stone, Neil J.; Bailey, Alison L.; Beam, Craig; Birtcher, Kim K.; Blumenthal, Roger S.; Braun, Lynne T.; de Ferranti, Sarah; Faiella-Tommasino, Joseph; Forman, Daniel E.; Goldberg, Ronald; Heidenreich, Paul A.; et al.
Abstract : Supplemental Digital Content is available in the text.